Extreme Programming Study Method Case Study on Designing of Accounting Term Dictionary - Usman Ependi; Qoriani Widayati (Universitas Bandar Lampung (UBL), 2013)
Extreme Programming (XP) is a software development method that is simple and includes one of the agile methods pioneered by Kent Beck, Ron Jeffries, and Ward Cunningham. The main purpose of the Extreme Programming method is to reduce the cost of software changes, in traditional systems development methodologies, system requirements specified in the first phase of the project development and it is not changed. This means that the cost to the needs of the change that occurs in the later stages will be very expensive. The Results of this study are to determine how the weaknesses and strengths of the XP method of making an application accounting terms dictionary on a Smartphone.